Developing a measurement tool for hospital service excellence / Voon Boo Ho ... [et al.] - Voon, Boo Ho; Abdullah, Firdaus; Lee, Nagarajah; Karen, Kueh Meng Koon (2012)
The employee-perceived service culture and customer-perceived service quality are commonly regarded as important for enhancing the quality perceptions, satisfaction and loyalty of the key stakeholders. This is also found to be true for the hospitals. This measurement-based survey research aims to development a multi-item measurement tool for hospital service excellence, from the employee's perspective. It can measure the culture of service excellence for hospitals.